The Horrell Wars : Feuding in Texas and New Mexico - Johnson, David (Book collections on Project MUSE., 2014)
For decades the Horrell brothers of Lampasas, Texas, have been portrayed as ruthless killers and outlaws, but author David Johnson paints a different picture of these controversial men. The Horrells were ranchers, but some thought that they built their herds by rustling. Their initial confrontation with the State Police at Lampasas in 1873 marked the most disastrous shootout in Reconstruction history.